Physical activity during holidays as a factor in reducing feelings of psychophysical fatigue among managers - Vođević, Vladan D; Nešić, Milan (Poslovna ekonomija, 2021)
The inevitable companion of managerial work is intense psychophysical stress. Its sources are located in the entire living and working environment of a person, and managerial work requires inevitable and constant interaction with the internal and external environment. In addition to factors related to the characteristics of the workplace, the source of psychophysical fatigue among managers is considered to be the current lifestyle. One of the reference areas that can be used to raise awareness of the benefits of regular physical activity among managers, and to influence the beginning of their regular application, is the concept of active rest.The empirical research, which was conducted on a sample of 50 managers from several Belgrade business organizations, aimed to identify certain aspects of physical activity during the summer vacation, which may be factors in reducing feelings of psychophysical fatigue. The results showed that managers, both genders, although they do not have regular physical exercise in their life habits, show some interest in additional use of some sports and recreational facilities during the holidays, which resulted in a significant reduction of psychophysical fatigue symptoms.
Keywords: managers, psychophysical fatigue, active rest